Peningkatan hasil belajar siswa pada pembelajaran IPS dengan menggunakan model Cooperative Learning tipe Talking Stick di Kelas V SDN 22 Tanah Keras Kabupaten Pesisir Selatan - aprima, tesa; farida s, Farida s; harni, harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe the improvement of student learning outcomes in PKn learning with Cooperative Learning model type Talking Stick in class IV SD Negeri 01 Bandar Buat. The approach used is qualitative and quantitative. The subjects were  teachers and 30 students. The results of this study indicate improvement in student learning outcomes. In cycle I obtained the average percentage of student learning outcomes 79,1 and on the  cycle II is 87,3. Thus, cooperative model type Talking Stick can improve student learning outcomes in learning Civics in class V SD Negeri 22 Tanah Keras Kabupaten Pesisir Selatan..  Keywords: study yield, sociology, Cooperative Learning, Talking Stick